Violence Against North Korean Refugee Women: Doubly Victimized By Repatriation and Premigration Traumatic Experiences - Kim, Eunyoung (Violence against women, 2022)
This study investigates the influence of traumatic events on the mental health of North Korean refugee women by examining the prevalence and severity of posttraumatic stress disorder (PTSD), depression, and anxiety in comparison with their male counterparts (women = 496; men = 131). Our results suggest that women are at greater risk of developing mental health problems than men. In particular, symptoms of PTSD and anxiety were higher among women who experienced forced repatriation to North Korea, which is operationalized as a constellation of gendered traumatic incidents such as sexual abuse, rape, witnessing infanticides, and forced abortion. The policy implications of our results and suggestions for future studies are discussed.